GENDER IMBALANCE IN THE ACADEMIA IN NIGERIA - Olaogun, James Adeola; Adebayo, Anthony Abayomi; Oluyemo, Catherine Ajoke (European Scientific Journal, ESJ, 2015)
The fact that there is gender imbalance at work and in social institutions continues to generate debates, discussions and concerns. Women have somewhat experienced gender opportunity restrictions and ceiling across societies down the ages. What is problematic is the consistency and persistence of the imbalance in Nigeria even when change is constant and reverberating around the globe. A survey of selected tertiary institutions in Nigeria revealed that there is gender imbalance in the constitution of the faculty staff. The men clearly outnumber the women. The paper proffers that for rapid societal development and greater sense of belonging, the discrimination against women should stop, especially in the academia who uphold the citadel of learning and that gender sensitivity in appointments should be put at the front burner.